The Philosophy and Elasticity of Zakah Distribution in Islam - Wan Khairuldin, Wan Mohd Khairul Firdaus; Mohammad, Mahadi (2013)
Islam has its own philosophy in all the prescribed laws, including zakah. Zakah is one of the mechanism in distributing wealth and social balance processes sanctioned by Islam. The paper attempts to discover the philosophy of zakah especially zakah distribution in its governance. The paper is library-based research on Islamic primary sources (al-Quran and al-Hadith) and secondary sources (Scripture scholars) to identify the philosophy in implementation of zakah. The philosophy of zakah implementation is identified by reviewing the zakah distribution and rate allocated to every zakah recipients. Through a compilation of Islamic juristical and implicit objectives in zakah distribution, the study highlights the philosophy of justice is the top priority in zakah distribution’s aim. This paper also highlights the concepts that support philosophy of justice in zakah distribution. Among those concepts are Istikhlaf (replacement) and Takaful (solidarity). The paper also review about scope of Ijtihad in zakah distribution based on needs and elasticity of recipients, the distribution’s rate and form of distribution. Findings from this study can guide the zakah institutions to achieve efficiency in the distribution in the future.